Motivational Dynamics in Education: Exploring Current Learning Theories - Muhammad Nurhidayat; Handayaningrum, Warih (Berpusi Publishing, 2024)
This article explains the dynamics of motivation in education with an emphasis on contemporary learning theories. Motivation is identified as the main psychological factor that influences the learning process. This article also discusses contemporary educational theories, such as constructivism, connectivism, self-determination theory (SDT), and social cognitive theory. This research uses a literature study methodology to analyze concepts and determine their implications for student motivation in an educational context. Research findings show that SDT theory prioritizes autonomy, social competence, and interpersonal relationships as key components for increasing student motivation. In education, Social Cognitive Theory emphasizes observation and modelling, while Constructivism advocates active learning and the relevance of material to students' daily lives. Especially in the digital era, connectivism emphasizes the importance of information networks and collaboration in education. Integrating key aspects of these theories can provide a foundation for responsive and holistic learning strategies, creating learning environments that are stimulating, relevant, and motivating for students across the educational spectrum.